Letter: the outcome of ulcerative colitis patients undergoing pouch surgery may be determined by pre‐surgical factors. Authors' reply. Issue 9 (11th October 2017) - Yanai, H.; Ben‐Shachar, S.; Mlynarsky, L.; Godny, L.; Leshno, M.; Tulchinsky, H.; Dotan, I.
Abstract : This article is linked to Ayubi and Safiri, and Yanai et al papers. To view these articles visithttps://doi.org/10.1111/apt.14255 andhttps://doi.org/10.1111/apt.14205 .